ANALISIS PENERIMAAN PAJAK TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN TAKALAR - Bangsawan, Reni Nara; Sahade, Sahade; Tikollah, M Ridwan (Universitas Jabal Ghafur, 2024)
This research aims to determine Tax Revenue from Original Regional Income at the Takalar Regency Regional Revenue Agency Office. The variable in this research is the Analysis of Tax Revenues on Original Regional Income (Case Study of the Takalar Regency Regional Revenue Agency). The population of this study is all data from reports on the realization of Regional Original Income (PAD) while the sample in this study is data on the realization of Regional Original Income (PAD). Data collection techniques are interviews and documentation. The data analysis techniques used are contribution analysis and effectiveness analysis. The results of this research show an analysis of the contribution of tax revenue to local original income in 2020 of 27.54% in the medium category, in 2021 it was 20.30% in the medium category and in 2022 it was 20.24 in the medium category. From the results of the effectiveness and contribution analysis, it can be seen that the average effectiveness is not effective and the average contribution analysis is moderate. Meanwhile, the results of research analyzing the effectiveness of regional taxes for the period 2020 to 2022, in 2020 the effectiveness level was 96.14% in the effective category, while in 2021 it was 50.70% in the ineffective category and in 2022 the effectiveness level was 46. 61 in the ineffective category.